Nim al-Quran - Miftahul Jannah (MAGHZA, 2018)
This paper intends to further examine the concept of Niáº“Äm al-Qurâ€™Än which is promoted by al-FarÄhi as the basis of its interpretation method. Thus, this paper places Niáº“Äm al-Qurâ€™Än as a material object and al-FarÄhi as its formal object. The significance of this study is not only to see the wealth of the method of interpretation of the Qur'an but as a form of the development of the interpretation method itself. In addition, it shows the pattern of development in the realm of interrelated interpretive methods. In this case, al-FarÄhi acknowledged what he was discussing - Niáº“Äm al-Qurâ€™Än - not something new, but he also emphasized the originality of the niáº“Äm concept. The concept of Niáº“Äm al-Qur'an for him is different from the concept of munÄsabah. Niáº“Äm al-Qur'an surpasses and munÄsabah is part of it, not vice versa. From this concept, there appear wahdaniyah terms and â€˜Amud. The first term is the difference between the two previous nomenclature and one of the three important elements in the concept of Niáº“Äm al-Qur'an, besides tartÄ«b and tanÄsub. The second term is the central or central theme of each letter.